2016
DOI: 10.1002/jobm.201500648
|View full text |Cite
|
Sign up to set email alerts
|

Two isocitrate dehydrogenases from a plant pathogen Xanthomonas campestris pv. campestris 8004. Bioinformatic analysis, enzymatic characterization, and implication in virulence

Abstract: Isocitrate dehydrogenase (IDH) is a key enzyme in the tricarboxylate (TCA) cycle, which may play an important role in the virulence of pathogenic bacteria. Here, two structurally different IDHs from a plant pathogen Xanthomonas campestris pv. campestris 8004 (XccIDH1 and XccIDH2) were characterized in detail. The recombinant XccIDH1 forms homodimer in solution, while the recombinant XccIDH2 is a typical monomer. Phylogenetic analysis showed that XccIDH1 belongs to the type I IDH subfamily and XccIDH2 groups in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
4
8
0
Order By: Relevance
“…Interestingly, even though the H 604 L/R 615 D/R 664 S mutant enzyme could utilize NAD + as the coenzyme, the catalytic efficiency was fairly low. Similar results were obtained in other studies that sought to convert the coenzyme dependence of IDH from NADP + to NAD + , such as for M. methylutens IDH (Wang et al, 2020), X. fastidiosa IDH (Lv et al, 2018), and X. campestris IDH (Lv et al, 2016) (Supplementary Table S2). These results indicated that additional amino acid residues are involved in the binding of NAD + by monomeric IDHs, and further imply that the mechanisms involved in NAD + catalysis are more complex than those involved in NADP + catalysis in the type III IDH subfamily.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, even though the H 604 L/R 615 D/R 664 S mutant enzyme could utilize NAD + as the coenzyme, the catalytic efficiency was fairly low. Similar results were obtained in other studies that sought to convert the coenzyme dependence of IDH from NADP + to NAD + , such as for M. methylutens IDH (Wang et al, 2020), X. fastidiosa IDH (Lv et al, 2018), and X. campestris IDH (Lv et al, 2016) (Supplementary Table S2). These results indicated that additional amino acid residues are involved in the binding of NAD + by monomeric IDHs, and further imply that the mechanisms involved in NAD + catalysis are more complex than those involved in NADP + catalysis in the type III IDH subfamily.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, the K m values of PtIDH2 for NADP + were 37.37 ± 4.02 μM with Mn 2+ and 18.37 ± 2.94 μM with Mg 2+ , and the corresponding catalytic efficiency (k cat /K m ) values were 3.22 and 2.36 μM −1 s −1 (Supplementary Figure S2). These k cat /K m values were similar to those for the bacterial monomeric NADP-IDHs from Xanthomonas campestris (6.0 μM −1 s −1 with Mn 2+ ) and Streptomyces avermitilis (11.7 μM −1 s −1 with Mn 2+ ) (Wang et al, 2011;Lv et al, 2016), but higher than those for the homodimeric NADP-IDH (contains two monomeric IDH-like subunits) from A. baumannii (0.39 μM −1 s −1 with Mn 2+ ) (Wang et al, 2018) and lower than those for the monomeric IDHs from A. vinelandii (15.0 μM −1 s −1 with Mn 2+ ) and Xylella fastidiosa (96.5 μM −1 s −1 with Mn 2+ ) (Watanabe et al, 2005;Lv et al, 2018).…”
Section: Analysis Of Ptidh2 Kineticssupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, mAbIDH2 was totally abolished by incubation for 20 min at 45 °C while AbIDH2 still sustained 60% of the activity ( Figure 3 ). The results agree well with previous reports detailing that the monomeric IDHs were not stable above 25 °C [ 11 , 22 , 23 ]. It is not clear why the IDH2 from A. baumannii could bear a much higher temperature than that needed for normal growth.…”
Section: Resultssupporting
confidence: 93%
“…psychrerythraea and X . campestris have one homodimeric type I IDH and one monomeric IDH with different biochemical properties [810]. Most prokaryotic IDHs that have been investigated are NADP + -dependent and homodimeric [1117].…”
Section: Introductionmentioning
confidence: 99%